Synthesis and physicochemical properties of hydrophobic uv curable fluoroacrylate-palm oil polyurethane coating - Mohamad Ismail, Mohamad Isa (2024)
Fluoroacrylate has been widely known for its low surface energy properties and is used as a monomer to increase polymer hydrophobicity properties. However, the fluoro chain lengths and functionalities also affect the other polymer properties such as thermal and mechanical. Driven by these understandings, this study was conducted on palm oil polyurethane (POPU) modification using fluoroacrylate monomer at different concentrations. Further analysis of microstructure, morphology, hydrophobicity, and physical and thermal properties was studied to evaluate the effect of fluoroacrylate on POPU polymers. The synthesis process started with an acrylation reaction of epoxidized palm oil (EPO) to form acrylated epoxidized palm oil (AEPO) and followed by an isocyanation reaction to form POPU oligomer. Then, the POPU oligomer was added with other types of monomers such as trimethylolpropane triacrylate (TMPTA) and 1,6 hexamethyl diacrylate (HDDA), together with fluoroacrylate monomer and benzophenone as the photoinitiator. Finally, the sample was cast on silicone mould at 1 mm thickness and cured under ultraviolet (UV) radiation for 1 minute. FTIR analysis confirmed the success of the synthesis process. The synthesis of AEPO was proven successful as the peak C=C peak (1631 cm-1 ) appeared which indicates successful acrylate attachment to EPO. Analysis proceeded with POPU reaction and the absence of isocyanate peak (2000-2500 cm-1 ) and appearance of NH peak (3300 cm-1 ) showed a successful isocyanation reaction. In fluoroacrylate palm oil polyurethane (FPOPU) synthesize, C-F group (1023 cm-1 ) peak showed the successful attachment of fluoroacylate monomer to POPU. The chemical structure elucidation was also successfully done by NMR on AEPO and POPU. In 1H NMR analysis, C=C group was detected at 2.0-3.0 ppm and OH peak at 3.687 ppm. For POPU, peak at 3.0 ppm in 1H NMR analysis suggested that NH functional has formed. In 13C NMR, the existence of urethane linkage at 172 ppm further confirmed the reaction. The addition of fluoroacrylate monomer in POPU showed an increase in surface roughness and provide a self-wrinkle pattern which significantly improved the hydrophobic properties of FPOPU. Water contact angle increased significantly by 136% (6 phr), sliding angle 55.33% by (2 phr), and water absorption by 26.7% (6 phr). The thermal characterization indicates that the addition of fluoroacrylate at high concentrations decreased the melting temperature and glass transition temperature of POPU polymer. The lowest melting temperature was recorded at 309 ℃ and the glass transition temperature at 120.3 ℃ at 10 php fluoroacrylate monomer addition. Thermal degradation at 6 phr improved by 8.47% (T5%), 10.77% (T10%), and 0.72% (T50%). In XRD analysis, the amorphous peak at 20° becomes smaller as more fluoroacrylate monomer was added and crosslinking activity decreased by 5% (12 phr) as fluoroacrylate was added. This phenomenon further indicates that arrangement of the molecule changes from high ordered to less ordered at high fluoroacrylate additions (8-12 phr). For physical analysis, FPOPU showed excellent adhesion at steel surface at 6 phr and hardness of FPOPU decreased at high fluoroacrylate addition (8-12 phr). The highest hardness was recorded at 6 phr on steel surface (8H).